THE CULTURE OF DIALOGUE AND THE PRAGMATIC ESSENCE OF GREETING UNITS IN THE WORKS OF SAID AHMAD - Geldiyeva Oʻgʻiloy Eli qizi (Bright Mind Publishing, 2025)
The article examines acts of greeting speech in relation to cultural values, social status and speech ethics of the Uzbek people. The author elucidates the communicative functions of greeting forms in literary texts, their contextual meaning and role in expressing the relationship between participants in the dialogue.
Keywords: Culture of communication, greeting units, linguistic pragmatics, act of speech, artistic discourse, communicative situation, sociolinguistics, national mentality, ethical principles.